Experimental investigation of the aeroacoustics of synthetic jet actuators in quiescent conditions - Jeyalingam, Jonne; Jabbal, Mark (Elsevier, 2018)
In this paper, the aeroacoustic characteristics of a circular orifice, synthetic jet actuator in quiescent conditions is investigated. Electromagnetic actuation, in the form of a shaker-driven actuator with latex diaphragm, proved to be desirable over piezoelectric actuation for this work due to the reduced diaphragm noise contribution to overall actuator self-noise, hence making it easier to identify jet-related noise. Acoustic and velocity data, collected from microphone measurements in an anechoic chamber and hotwire measurements respectively, were compared for correlation. Schlieren visualization was also used to show synthetic jet development near the orifice. Flow-induced sound in the form of an audible whistling was found to occur for a Strouhal number range of 0.24